Animal Migration Optimization: A Survey - Rai, Riya; Singh Kushwah, Virendra (International Journal of Computer Sciences and Engineering, 2025)
A new swarm intelligent algorithm, called as Animal Migration Optimization (AMO). This paper discusses brief introduction of few optimization techniques. Optimization techniques used for finding optimal solutions. The efficiency of AMO is not appropriate due to its execution time. The efficiency of animal migration optimization algorithm (AMO )is increase by using few benchmark functions and which show the animal migration algorithm performance and it’s working in order to confirm the presentation of AMO including four benchmark functions – Sum, Ackley, Baele and Rosenbrock are employed. The benchmark functions which are considered as standard functions increase the efficiency and minimize the time.